Breast cancer and occupation: Non-parametric and parametric net survival analyses among Swiss women (1990–2014) - Guseva Canu, Irina; Bovio, Nicolas; Arveux, Patrick; Bulliard, Jean-Luc; Fournier, Evelyne; Germann, Simon; Konzelmann, Isabelle; Maspoli, Manuela; Rapiti, Elisabetta; Grzebyk, Michel (Frontiers in Public Health, 2023)
Introduction Occupation can contribute to differences in risk and stage at diagnosis of breast cancer. This study aimed at determining whether occupation, along with skill level and the socio-professional category, affect the breast cancer survival (BCS) up to 10 years after diagnosis. Materials and methods We used cancer registry records to identify women diagnosed with primary invasive breast cancer in western Switzerland over the period 1990–2014 and matched them with the Swiss National Cohort. The effect of work-related variables on BCS was assessed using non-parametric and parametric net survival methods. Results Study sample included 8,678 women. In the non-parametric analysis, we observed a statistically significant effect of all work-related variables on BCS. Women in elementary occupations, with low skill level, and in paid employment not classified elsewhere, had the lowest BCS, while professionals, those with the highest skill level and belonging to top management and independent profession category had the highest BCS. The parametric analysis confirmed this pattern. Considering elementary occupations as reference, all occupations but Craft and related trades had a hazard ratio (HR) below 1. Among professionals, technicians and associate professionals, and clerks, the protective effect of occupation was statistically significant and remained unchanged after adjustment for age, calendar period, registry, nationality, and histological type. After adjusting for tumor stage, the HRs increased only slightly, though turned non-significant. The same effect was observed in top management and independent professions and supervisors, low level management and skilled laborers, compared to unskilled employees. Conclusion These results suggest that work-related factors may affect BCS. Yet, this study was conducted using a limited set of covariates and a relatively small study sample. Therefore, further larger studies are needed for more detailed analyses of at risk occupations and working conditions and assessing the potential interaction between work-related variables and tumor stage.